2020
DOI: 10.1016/j.tipsro.2020.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Personalised treatment for older adults with cancer: The role of frailty assessment

Abstract: It is widely accepted in clinical practice that chronological age is a poor predictor of treatment tolerance and outcomes in older adults with cancer. Intrinsic vulnerability is more a function of underlying frailty, rather than chronological age. Frailty is a state of increased vulnerability to stressors, such as cancer and its treatment, which can lead to adverse health outcomes for patients. Capturing this heterogeneity in reserve capacity is the cornerstone of management in geriatricmedicine, but remains p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 148 publications
(164 reference statements)
0
13
0
1
Order By: Relevance
“…Older patients are more likely to be strictly selected for aggressive treatments probably because of poor general condition, preexisting comorbidities, increased toxicity during chemotherapy [ 13 ], reluctance of clinicians/patients to offer/undergo surgery [ 4 ], longer hospital stay, and higher in-hospital mortality rates [ 14 ]. Identifiable comorbidities and frailty changes due to aging can limit a patient’s ability to tolerate cancer therapy [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Older patients are more likely to be strictly selected for aggressive treatments probably because of poor general condition, preexisting comorbidities, increased toxicity during chemotherapy [ 13 ], reluctance of clinicians/patients to offer/undergo surgery [ 4 ], longer hospital stay, and higher in-hospital mortality rates [ 14 ]. Identifiable comorbidities and frailty changes due to aging can limit a patient’s ability to tolerate cancer therapy [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…CGA in older cancer patients indicates previously unknown geriatric problems in many patients (up to 50%) and may alter treatment decisions in 10-20% of patients [19]. Among the domains of CGA, limitations in cognition, nutrition, function, and comorbidities have been shown to be important factors in diminishing OS in older cancer patients in several studies [20][21][22]. It has also been shown that specialized geriatric intervention for older cancer patients signi cantly improved OS and facilitated a return to their own home compared to conventional care.…”
Section: Discussionmentioning
confidence: 99%
“…The gold standard of clinical assessment of frailty is the CGA. As this is a time-consuming tool and requires some training, screening tools such as the clinical frailty scale, the frailty phenotype, or the frailty index can be used as a preliminary step to select patients for CGA [ 120 ].…”
Section: Discussionmentioning
confidence: 99%